Modulation of cortical slow oscillatory rhythm by GABAB receptors: an in vitro experimental and computational study. (18th June 2020) - Perez‐Zabalza, Maria; Reig, Ramon; Manrique, Jesus; Jercog, Daniel; Winograd, Milena; Parga, Nestor; Sanchez‐Vives, Maria V.
Abstract : Key points: We confirm that GABAB receptors (GABAB ‐Rs) are involved in the termination of Up‐states; their blockade consistently elongates Up‐states. GABAB ‐Rs also modulate Down‐states and the oscillatory cycle, thus having an impact on slow oscillation rhythm and its regularity. The most frequent effect of GABAB ‐R blockade is elongation of Down‐states and subsequent decrease of oscillatory frequency, with an increased regularity. In a quarter of cases, GABAB ‐R blockade shortened Down‐states and increased oscillatory frequency, changes that are independent of firing rates in Up‐states. Our computer model provides mechanisms for the experimentally observed dynamics following blockade of GABAB ‐Rs, for Up/Down durations, oscillatory frequency and regularity. The time course of excitation, inhibition and adaptation can explain the observed dynamics of the network. This study brings novel insights into the role of GABAB ‐R‐mediated slow inhibition on the slow oscillatory activity, which is considered the default activity pattern of the cortical network. Abstract: Slow wave oscillations (SWOs) dominate cortical activity during deep sleep, anaesthesia and in some brain lesions. SWOs are composed of periods of activity (Up states) interspersed with periods of silence (Down states). The rhythmicity expressed during SWOs integrates neuronal and connectivity properties of the network and is often altered under pathological conditions. Adaptation mechanisms as well as synaptic inhibition mediated by GABAB receptors (GABAB ‐Rs) have been proposed as mechanisms governing the termination of Up states. The interplay between these two mechanisms is not well understood, and the role of GABAB ‐Rs controlling the whole cycle of the SWO has not been described. Here we contribute to its understanding by combining in vitro experiments on spontaneously active cortical slices and computational techniques. GABAB ‐R blockade modified the whole SWO cycle, not only elongating Up states, but also affecting the subsequent Down state duration. Furthermore, while adaptation tends to yield a rather regular behaviour, we demonstrate that GABAB ‐R activation desynchronizes the SWOs. Interestingly, variability changes could be accomplished in two different ways: by either shortening or lengthening the duration of Down states. Even when the most common observation following GABAB ‐Rs blocking is the lengthening of Down states, both changes are expressed experimentally and also in numerical simulations. Our simulations suggest that the sluggishness of GABAB ‐Rs to follow the excitatory fluctuations of the cortical network can explain these different network dynamics modulated by GABAB ‐Rs. Key points: We confirm that GABAB receptors (GABAB ‐Rs) are involved in the termination of Up‐states; their blockade consistently elongates Up‐states. GABAB ‐Rs also modulate Down‐states and the oscillatory cycle, thus having an impact on slow oscillation rhythm and its regularity. The most frequent effect of GABAB ‐R blockade is elongation of Down‐states and subsequent decrease of oscillatory frequency, with an increased regularity. In a quarter of cases, GABAB ‐R blockade shortened Down‐states and increased oscillatory frequency, changes that are independent of firing rates in Up‐states. Our computer model provides mechanisms for the experimentally observed dynamics following blockade of GABAB ‐Rs, for Up/Down durations, oscillatory frequency and regularity. The time course of excitation, inhibition and adaptation can explain the observed dynamics of the network. This study brings novel insights into the role of GABAB ‐R‐mediated slow inhibition on the slow oscillatory activity, which is considered the default activity pattern of the cortical network.